El uso de isótopos radioactivos y de radiaciones en la agricultura tropical - Boroughs, Howard (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
A brief discussion of the problems and promises of using radiations and radioisotopes in the developing tropical countries is presented. Specific progress reports in this field have been given for India, where most of the work has been done, but also in Iran, Pakistan, Thailand, Burma, Philippines, Taiwan, Hawaii, Congo, Ghana, Morocco, Tunisia, Mali, Sudan, Puerto Rico, Trinidad, Mexico, Brazil, Ecua-dor, Venezuela, Pern, Guatemala, Panama, and at the Interamerican Institute of Agricultural Sciences, in Turrialba.